Ilustración de aves comunes del campus de la Universidad del Quindío: Guía de campo (2016)
In this paper the Scientific Enlightenment and ornithological knowledge so that illustrated and described the common birds of the campus of the University of Quindio, located in the city of Armenia was articulated, because so far there was no material disclosure of this kind. The birds were selected on the basis of the study by Guerrero et al., (2014). For editing images and specialized freeware program GIMP 2.8.10 and 1.4.5 Scribus free access to the design and layout was used. The guide "Birdlife Campus of the University of Quindio: Illustrated Guide" has 39 illustrations of common bird species grouped into 18 families, with 27 species located in the Passeriformes order, and 12 species not Passeriformes. Humid Andean Forests and: Among the above kind located in the category of vulnerable species according to Global Classification of the International Union for Conservation of Nature (IUCN) and the Red Book of Birds of Colombia, Volume I stood Pacific coast Renjifo et al., (2014) Dacnis turquoise (Dacnis hartlaubi) that like stippling Piculet (Picumnus granadensis) presents the endemic condition for Colombia five almost-endemic Amazilia coliazul (Amazilia saucerrottei), Dark Cotorra (Pionus chalcopterus), Parakeet glasses (Forpus conspicillatus), Antshrike laugh (Thamnophilus multistriatus) and Tangara rastrojera (Tangara vitriolina) in accordance with Schedule Updated endemic Bird and almost-endemic Chaparro-Herrera et al., (2013) and boreal immigration Blackburnian Warbler (Setophaga fusca). The guide was presented by synthesizing relevant aspects of their biology information and is designed in such a way that can be interpreted by people not engaged in ornithology.